Mining sick: Creatively unsettling normative narratives about industry, environment, extraction, and the health geographies of rural, remote, northern, and Indigenous communities in British Columbia. (11th December 2020) - Aldred, Terri‐Leigh; Alderfer‐Mumma, Charis; de Leeuw, Sarah; Farrales, May; Greenwood, Margo; Hoogeveen, Dawn; O'Toole, Ryan; Parkes, Margot W.; Sloan Morgan, Vanessa
Abstract : Rural, remote, northern, and Indigenous communities on Turtle Island are routinely—as Cree Elder Willie Ermine says—pathologized. Social science and health scholarship, including scholarship by geographers, often constructs Indigenous human and physical geographies as unhealthy, diseased, vulnerable, and undergoing extraction. These constructions are not inaccurate: peoples and places beyond urban metropoles on Turtle Island live with higher burdens of poor health; Indigenous peoples face systemic violence and racism in colonial landscapes; rural, remote, northern, and Indigenous geographies are sites of industrial incursions; and many rural and remote geographies remain challenging for diverse Indigenous peoples. What, however, are the consequences of imagining and constructing people and places as "sick"? Constructions of "sick" geographies fulfill and extend settler (often European white) colonial narratives about othered geographies. Rural, remote, northern, and Indigenous geographies are discursively "mined" for narratives of sickness. This mining upholds a sense of health and wellness in southern, urban, Euro‐white‐settler imaginations. Drawing from multi‐year, relationship‐based, cross‐disciplinary qualitative community‐informed experiences, and anchored in feminist, anti‐colonial, and anti‐racist methodologies that guided creative and humanities‐informed stories, this paper concludes with different stories. It unsettles settler‐colonial powers reliant on constructing narratives about sickness in others and consequently reframes conversations about Indigenous well‐being and the environment . Key Messages: Myriad discourses converge to produce rural, remote, northern, and Indigenous geographies as pathologized spaces. Pathologizing rural, remote, northern, and Indigenous geographies leads to people and places being susceptible to discursive mining. New and different stories must be created and told about rural, remote, northern, and Indigenous geographies. Malade de l'industrie minière : la créativité troublante des discours normatifs sur l'industrie, l'environnement, l'extraction et la santé des communautés autochtones, nordiques et rurales en Colombie‐Britannique: Les communautés autochtones, nordiques et rurales de Turtle Island sont, comme le dit l'aîné cri Willie Ermine, couramment considérées comme pathogènes. Le discours professoral en sciences sociales et en santé, y compris chez les géographes, conçoit souvent les géographies autochtones, tant humaines que physiques, comme étant malsaines, malades, vulnérables et soumises à l'extraction. Ces conceptions ne sont pas erronées: les gens et les endroits en dehors des agglomérations urbaines sur Turtle Island sont davantage exposés à un état de santé précaire, les Autochtones font face à une violence et un racisme systémique dans les milieux coloniaux, les géographies autochtones, nordiques et rurales sont le siège d'incursions industrielles et de nombreux contextes territoriaux ruraux et éloignés continuent de présenter un défi pour diverses populations autochtones. Toutefois, quelles sont les conséquences d'imaginer et de concevoir les gens et les endroits comme étant « malades »? Le concept de territoires « malades » favorise et consolide les récits coloniaux (souvent le blanc européen) sur l'état d'autres territoires, lesquels seraient dans une situation plus favorable. Les géographies autochtones, nordiques et rurales sont alors « minées » de manière discursive par les récits sur leur caractère pathogène. Ce minage soutient une impression de santé et de bien‐être dans l'imaginaire colonial, blanc européen et urbain des populations du sud. S'inspirant d'expériences communautaires qualitatives éclairées interdisciplinaires pluriannuelles axées sur les relations et ancrées dans les méthodologies féministes, anticoloniales et antiracistes qui ont guidé les discours créatifs inspirés par les sciences humaines, le présent texte se termine avec des récits différents. Ceux‐ci déstabilisent les pouvoirs coloniaux qui se fondent sur le concept de territoire pathogène et, par conséquent, ré‐interprètent les perceptions et les affirmations sur l'environnement et le bien‐être des Autochtones .